Comparative analysis of postoperative curative effect of liver wedge resection and liver IVb + V segment resection in patients with T2b gallbladder cancer - Wang, Zichao; Liu, Hongliang; Huang, Yong; Wang, Jun; Li, Junjie; Liu, Lingpeng; Huang, Mingwen (Frontiers in Surgery, 2023)
Objective To compare the therapeutic effects of wedge resection and liver segment IVb + V resection on patients with T2b gallbladder cancer. Methods The clinical and pathological data of 40 patients with gallbladder cancer admitted to the Second Affiliated Hospital of Nanchang University from January 2017 to November 2019 were retrospectively analyzed, and they were divided into two groups according to different surgical methods. The control group underwent liver wedge resection, while the experimental group underwent liver segment IVb + V resection. Preoperative age, bilirubin index, tumor markers, postoperative complications and survival were compared between the two groups. Log-rank test was used for univariate analysis, and Cox proportional hazards regression model was used for multivariate analysis. Kaplan-Meier survival curves were drawn. Results Univariate analysis showed that tumor markers and degree of differentiation were the risk factors for the prognosis of patients with gallbladder carcinoma after radical cholecystectomy (P < 0.05). Multivariate analysis showed that the elevation of CA125 and CA199, poor differentiation, and Lymph node metastasis were independent risk factors for the prognosis of gallbladder carcinoma after radical resection (P < 0.05). According to the 3-year survival rate, the survival rate of patients with liver 4B + 5 segment resection + cholecystectomy was higher than that of patients with 2 cm liver wedge resection + cholecystectomy (41.6% vs. 72.7%). Conclusion Patients with T2b gallbladder cancer should be treated with liver segment IVb + V resection, which is helpful to improve the prognosis of patients and should be widely promoted.